The Effect of Picture Series in Writing Recount Text in SMPN 1 Malinau Barat - Sepura Cristine (Borneo Educational Journal (Borju), 2019)
Writing is an important major that should be mastered by students. However, it is hard for students to comprehend along English passage. The purpose of this study is to investigate the types of activities that occur during the teaching process of writing recount text through a series of pictures and to identify the benefits students receive from writing a recount text through a series of images. The total sampling technique is used in selecting samples. The results of the study revealed that teaching writing using a series of images can improve students' ability to write recount texts. In particular, they show some improvements to the process of writing and vocabulary.